Dakwah Mengenai Hak Asasi Manusia (HAM) Di Indonesia Dalam Konsep Maslahah Mursalah - Rojabi Azhargany (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2020)
Da'wah regarding Islamic values needs to be done in the community. Including, preaching about the Islamic values contained in the views that are being discussed in the public sphere, including about Human Rights (HAM). Democratic governance requires the existence of good governance, human rights and democracy. Obtaining the standards of democratic governance is needed by Indonesia to be internationally accepted. Nonetheless, Indonesia's record on human rights leads to the understanding that this country has to pay highly attention on human rights. Five basic rights in maqashid sharia (kulliyatul khoms) as important basic ideas to be elaborated into values ​​that are included in the effort to realize good governance. Keywords: Da’wah, good governance, human rights, kulliyatul khoms